Relationship between air pollution, lung function and asthma in adolescents. Issue 11 (21st May 2007) - Islam, Talat; Gauderman, W James; Berhane, Kiros; McConnell, Rob; Avol, Ed; Peters, John M; Gilliland, Frank D
Abstract : Background: The interrelationships between air pollution, lung function and the incidence of childhood asthma have yet to be established. A study was undertaken to determine whether lung function is associated with new onset asthma and whether this relationship varies by exposure to ambient air pollutants. Methods: A cohort of children aged 9–10 years without asthma or wheeze at study entry were identified from the Children's Health Study and followed for 8 years. The participants resided in 12 communities with a wide range of ambient air pollutants that were measured continuously. Spirometric testing was performed and a medical diagnosis of asthma was ascertained annually. Proportional hazard regression models were fitted to investigate the relationship between lung function at study entry and the subsequent development of asthma and to determine whether air pollutants modify these associations. Results: The level of airway flow was associated with new onset asthma. Over the 10th–90th percentile range of forced expiratory flow over the mid-range of expiration (FEF25–75, 57.1%), the hazard ratio (HR) of new onset asthma was 0.50 (95% CI 0.35 to 0.71). This protective effect of better lung function was reduced in children exposed to higher levels of particulate matter with an aerodynamic diameter <2.5 μm (PM2.5 ). Over the 10th–90th percentile range of FEF25–75, the HR of new onset asthma was 0.34 (95% CI 0.21 to 0.56) in communities with low PM2.5 (<13.7 μg/m 3 ) and 0.76 (95% CI 0.45 to 1.26) in communities with high PM2.5 (⩾13.7 μg/m 3 ). A similar pattern was observed for forced expiratory volume in 1 s. Little variation in HR was observed for ozone. Conclusion: Exposure to high levels of PM2.5 attenuates the protective effect of better lung function against new onset asthma.